The Improvement of Drama Writing Skill of Grade VIII Students at Junior High School - Yantri Indayarsi (Universitas Negeri Padang, 2019)
Based on the problem in teaching Bahasa Indonesia at school, the researcher considers that the research entitled “The Improvement of Drama Writing Skill of Grade VIII students at SMPN 18 Malang by The Use of School Environment” is good to be applied. Writing drama is the form of writing which is beneficial for students. By writing drama, students can (1) express themselves (2) improve vocabulary well and in vary, (3) identify objects, events and certain situations. The problem of the research is how grade VIII students’ drama writing skill at SMPN 18 Malang is by the use of school environment. The purpose of the research is to describe how grade VIII students’ drama writing skill at SMPN 18 Malang is by the use of school environment. The research uses Classroom Action Research. It is hold at SMPN 18 Malang. It is situated at Jalan Soekarno Hatta A-394 Malang. It is began with the preliminary study on March 2018. As the research target is all students of grade VIII so that the research subject is the students of grade VIII of SMPN 18 Malang in the second semester in 2017-2018. The numbers of research subject is 32 students. The data analysis can be applied during the research or before the research by based on the process and result of students learning. The results of the research are 1 The improvement of drama writing process in class VIII of SMPN 18 Malang by using school environment is enthusiastic, focused and active in following learning process starting from the beginning until the last. (2) the improvement of achievement in drama writing study starting from the first reflection until the application of cycle 1 and cycle 2. The failure is degraded from the first reflection achieving 25 students to 14 students in cycle 1 and it passes in cycle 2 or 100% passes. Having the lowest score of 65 in the pre-cycle, it improves into 70 in cycle 1 and improves into 80 in cycle 2. The classical average is increasing from 75 to 79 in cycle 1 and increasing to 85 in cycle 2. Accordingly, the improvement of drama writing skill by the use of school environment can be proved. In summary, the improvement of drama writing skill in grade III at SMPN 18 Malang can be developed by the use of school environment. As a suggestion for Bahasa Indonesia teachers, they should (a) place the students as a center of learning activity (2) give direction and motivation for students to write drama scripts.Keywords: Improvement, Drama Writing Skill, The Use Of School Environment